Biochemical characterization in Norway spruce (Picea abies) of SABATH methyltransferases that methylate phytohormones. (May 2018) - Chaiprasongsuk, Minta; Zhang, Chi; Qian, Ping; Chen, Xinlu; Li, Guanglin; Trigiano, Robert N.; Guo, Hong; Chen, Feng
Abstract: Indole-3-acetic acid (IAA), gibberellins (GAs), salicylic acid (SA) and jasmonic acid (JA) exist in methyl ester forms in plants in addition to their free acid forms. The enzymes that catalyze methylation of these carboxylic acid phytohormones belong to a same protein family, the SABATH methyltransferases. While the genes encoding these enzymes have been isolated from a small number of flowering plants, little is known about their occurrence and evolution in non-flowering plants. Here, we report the systematic characterization of the SABATH family from Norway spruce ( Picea abies ), a gymnosperm. The Norway spruce genome contains ten SABATH genes ( PaSABATH1-10 ). Full-length cDNA for each of the ten PaSABATH genes was cloned and expressed in Escherichia coli . Recombinant PaSABATHs were tested for activity with IAA, GA, SA, and JA. Among the ten PaSABATHs, five had activity with one or more of the four substrates. PaSABATH1 and PaSABATH2 had the highest activities with IAA and SA, respectively. PaSABATH4, PaSABATH5 and PaSABATH10 all had JA as a preferred substrate but with notable differences in biochemical properties. The structural basis of PaSABATHs in discriminating various phytohormone substrates was inferred based on structural models of the enzyme-substrate complexes. The phylogeny of PaSABATHs with selected SABATHs from other plants implies that the enzymes methylating IAA are conserved in seed plants whereas the enzymes methylating JA and SA have independent evolution in gymnosperms and angiosperms. Graphical abstract: The gymnosperm Norway spruce contains three jasmonic acid methyltransferase genes, which appear to have evolved independently from those in angiosperms.Image 1 Highlights: The Norway spruce 10-member SABATH family include one IAMT, one SAMT and three JAMTs . IAMTs are conserved in seed plants. JAMT evolved independently in gymnosperms and angiosperms.